Determinants of Halal Cosmetics Purchase Intention in Gen-Z: An Empirical Study in Java Island - Muhammad Iqbal Mahdi; Ali Azhar, Jeihan; Imam Basri, Anindita (FEBI UIN Sunan Kalijaga, 2025)
This study aims to analyze the influence of halal marketing, halal labeling, knowledge, brand image, and product quality on the interest in buying halal cosmetics in the Zilenial generation.The method used in this study is a quantitative survey approach through a questionnaire with a sample of 211 Gen-Z respondents who were selected by purposive sampling based on birth criteria between 1997-2012, domiciled on the island of Java and had bought halal cosmetic products. Data analysis was carried out using Structural Equation Modeling (SEM) technique. This study shows that halal marketing, halal labeling, halal knowledge, brand image, and product quality have a significant influence on buying interest. The implications of this research can be used by halal cosmetics industry players as a basis for formulating marketing strategies that are more effective and in accordance with the characteristics of Gen Z. By utilizing the right strategy, companies can help the country's economic growth.